El voluntariado entre la libertad y la necesidad social. - Pérez, Gabriel (Cuadernos de Relaciones Laborales, 2000)
The growing visibility of volunteering as a component of non-remunetated work is part of an underlying debate on the crisis in remunerated work asan essential tnearxs of distributing income and status. In this articíe, sonie estimates of the volume of non-remunerated, volunteerwork are ptít Iérward as well as the concurring conditions of freedom (for those receiving salaries). 11w need for this type of work is also analysed. Cm,emtie¡,,o de Reit¡r.iou¡es Lc¡bo¡ccies 123 2000,17:123-137 Gabriel Pérez Pérez El voluntariado entre la liberíad y la necesidad social
Keywords: Non-remunerated work; volunteering; new " deposits" * of employment; social cohesion